Prevalencia de parásitos intestinales en caninos de la ciudad de Machala - Ajila Moreira, Rosa Mercedes (2012)
This research on canine intestinal parasites was conducted in the city of Machala, based on the following objectives: 1) establish the prevalence of intestinal parasites in dogs in the city of Machala and 2) determine the prevalence according to their area of ​​origin , race, sex, age, type of food and habitat. It also determined the prevalence by gender of parasite, the methodology of the fieldwork was to be divided into areas (parishes) to the city of Machala to take stool samples of 300 apparently healthy animals, the same as those analyzed in the laboratory to determine variables, and was performed the Student t test in the sex variable. After the respective analysis and tabulation of the data could be obtained that the prevalence of intestinal parasites in dogs in the city of Machala, of the 300 animals tested, 90 were found to be positive for the presence of intestinal parasites, giving an infection percentage of 30%. According to the source the highest percentage was found in the parish Jambeli and doublets by 33.3%, depending on the size of the breed as many as were those of small size with 37.2% and the lowest in the 26.5% medium. Male dogs were compared 32.9% of females were 26.5%, children under 6 months were 40%. Domestic animals habitat had 31.3% higher this percentage being due to the risk of reinfection. Thus it was concluded that the animals evaluated to determine the prevalence of intestinal parasites in the case of Ancylostomas found 13% while Moscoso (2000) found 85% and Apollo (2007) 23.6% both investigations in the city of Machala, this decrease in prevalence is due to the influence of the veterinarian in a parasite control in pets.